The Effect of Employee Relations on Employee Performance Through Work Motivation at the Forestry Service of East Kalimantan Province - Ridho Adi Nugroho, Ridho Adi Nugroho; Istimaroh; Fitriansyah (Research in Management of Technology and Business, 2024)
This study aims to determine and analyze the effect of Employee Relations on Employee Performance through Work Motivation at the East Kalimantan Provincial Forestry Service. The population of this study were employees of the East Kalimantan Provincial Forestry Service. This research uses descriptive quantitative type. This study obtained a sample of 156 respondents who were taken by krejcie and morgan method using random sampling or all positions in the East Kalimantan Provincial Forestry Service. The data collection technique in this study used a questionnaire in the form of a Google Form. The data processing method in this study is to use IBM SPSS Version 26 and SmartPLS software version 4.0.2. The results of this study indicate that employee relations have a positive and significant effect on employee performance, employee relations have a positive and significant effect on work motivation, work motivation has a positive and significant effect on employee performance, and employee relations have a positive and significant effect on employee performance through work motivation.